Metal-free hydroarylation of the side chain carbon–carbon double bond of 5-(2-arylethenyl)-3-aryl-1,2,4-oxadiazoles in triflic acid - Zalivatskaya, Anna S.; Ryabukhin, Dmitry S.; Tarasenko, Marina V.; Ivanov, Alexander Yu.; Boyarskaya, Irina A.; Grinenko, Elena V.; Osetrova, Ludmila V.; Kofanov, Eugeniy R.; Vasilyev, Aleksander V. (Beilstein Journal of Organic Chemistry, 2017)
The metal-free reaction of 5-(2-arylethenyl)-3-aryl-1,2,4-oxadiazoles with arenes in neat triflic acid (TfOH, CF3SO3H), both under thermal and microwave conditions, leads to 5-(2,2-diarylethyl)-3-aryl-1,2,4-oxadiazoles. The products are formed through the regioselective hydroarylation of the side chain carbon–carbon double bond of the starting oxadiazoles in yields up to 97%. According to NMR data and DFT calculations, N4,C-diprotonated forms of oxadiazoles are the electrophilic intermediates in this reaction.
Keywords: Friedel–Crafts reaction; hydroarylation; oxadiazoles; superelectrophilic activation; triflic acid